Colorimetric biomimetic sensor systems based on molecularly imprinted polymer membranes for highly-selective detection of phenol in environmental samples - Sergeyeva, T.A.; Chelyadina, D.S.; Gorbach, L.A.; Brovko, O.O.; Piletska, E.V.; Piletsky, S.A.; Sergeeva, L.M.; El’skaya, A.V. (Вiopolymers and Cell, 2014)
Aim. Development of an easy-to-use colorimetric sensor system for fast and accurate detection of phenol in envi- ronmental samples. Methods. Technique of molecular imprinting, method of in situ polymerization of molecularly imprinted polymer membranes. Results. The proposed sensor is based on free-standing molecularly imprinted polymer (MIP) membranes, synthesized by in situ polymerization, and having in their structure artificial binding sites capable of selective phenol recognition. The quantitative detection of phenol, selectively adsorbed by the MIP membranes, is based on its reaction with 4-aminoantipyrine, which gives a pink-colored product. The intensity of staining of the MIP membrane is proportional to phenol concentration in the analyzed sample. Phenol can be detected within the range 50 nM–10 mM with limit of detection 50 nM, which corresponds to the concentrations that have to be detected in natural and waste waters in accordance with environmental protection standards. Stability of the MIP-membrane-based sensors was assessed during 12 months storage at room temperature. Conclusions. The sensor system provides highly-selective and sensitive detection of phenol in both mo- del and real (drinking, natural, and waste) water samples. As compared to traditional methods of phenol detection, the proposed system is characterized by simplicity of operation and can be used in non-laboratory conditions. Мета. Розробка простих у використанні колориметричних сенсорних систем для швидкого і точного визначення фенолу у зразках із довкілля. Методи. Метод молекулярного імпринтингу, метод полімеризації in situ молекулярно імпринтованих полімерних (МІП) мембран. Результати. Запропонований сенсор створено на основі МІП мембран, синтезованих методом полімеризації in situ, які мають у своїй структурі штучні рецепторні сайти зв’язування фенолу. Кількісне визначення фенолу, селективно адсорбованого МІП мембранами, грунтується на детекції забарвленого у малиновий колір продукту його реакції з 4-аміноантипірином. Інтенсивність забарвлення МІП мембран є пропорційною концентрації фенолу в аналізованому зразку. Фенол детектується у діапазоні 50 нМ–10 мМ, що відповідає концентраціям, які необхідно виявляти у природних і стічних водах. Стабільність сенсорних систем на основі МІП мембран становить12 місяців за кімнатної температури. Висновки. Сенсорні системи забезпечують високоселективний і чутливий аналіз фенолу як у модельних, так і реальних зразках (питна, природна, стічна вода). Порівняно до традиційних методів визначення фенолу пропонована система є простою у використанні та може бути застосована за польових умов. Цель. Разработка простых в использовании колориметрических сенсорных систем для быстрого и точного определения фенола в образцах из окружающей среды. Методы. Метод молекулярного импринтинга, метод полимеризации in situ молекулярно импринтированных полимерных (МИП) мембран. Результаты. Предложенный сенсор создан на основе МИП мембран, синтезированных методом полимеризации in situ, имеющих в своей структуре синтетические рецепторные сайты связывания фенола. Количественное определение фенола, селективно адсорбированного МИП мембранами, основано на детекции окрашенного в малиновый цвет продукта его реакции с 4-аминоантипирином. Интенсивность окрашивания МИП мембран пропорциональна концентрации фенола в анализируемом образце. Фенол можно детектировать в пределах 50 нМ–10 мМ, что соответствует концентрациям, которые необходимо выявлять в природных и сточных водах. Стабильность сенсорных систем на основе МИП мембран составляет 12 месяцев при комнатной температуре. Выводы. Сенсорные системы обеспечивают высокоселективный и чувствительный анализ фенола как в модельных, так и реальных образцах (питьевая, природная и сточная вода). По сравнению с традиционными методами определения фенола предложенная система проста в использовании и может применяться в полевых условиях.